2006
DOI: 10.1364/oe.14.007342
|View full text |Cite
|
Sign up to set email alerts
|

Design of photonic band gap fibers with suppressed higher-order modes: Towards the development of effectively single mode large hollow-core fiber platforms

Abstract: Abstract:The objective of the present investigation is to propose and theoretically demonstrate the effective suppression of higher-order modes in large-hollow-core photonic band gap fibers (PBGFs), mainly for low-loss data transmission platforms and/or high power delivery systems. The proposed design strategy is based on the index-matching mechanism of central air-core modes with defected outer core modes. By incorporating several air-cores in the cladding of the PBGF with 6-fold symmetry it is possible to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In this paper, we show that the suppression of HOMs in hollow-core PBGFs with realistic airholes in the cladding and core/cladding interface can be successfully achieved through the resonant-coupling mechanism of central air-core modes with defected outer core modes that we have proposed in [18]. Our primary target is derivation of a surface-mode-free condition for the silica-ring thickness surrounding the hollow core for both 7-unit-cell and 19-unit-cell air cores.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…In this paper, we show that the suppression of HOMs in hollow-core PBGFs with realistic airholes in the cladding and core/cladding interface can be successfully achieved through the resonant-coupling mechanism of central air-core modes with defected outer core modes that we have proposed in [18]. Our primary target is derivation of a surface-mode-free condition for the silica-ring thickness surrounding the hollow core for both 7-unit-cell and 19-unit-cell air cores.…”
mentioning
confidence: 80%
“…This fact can enable the index-matching mechanism to take place by bringing the two cores (19-unit-cell central core and 7-unit-cell outer core) close to each other, thus enabling resonant coupling over a certain wavelength regime. The phenomenon is expected to be enhanced further and to be a polarization-independent operation if we place more outer cores while keeping the sixfold symmetry around the central core in the PBGF as proposed in [18]. In order to enable the index-matching mechanism to occur between the HOM in 19-unit-cell core and the fundamental mode in 7-unit-cell core, we proceed by incorporating six 7-unit-cell cores into the cladding surrounding the central 19-unit-cell core to expect a polarization-independent operation, as shown in Fig.…”
Section: Suppression Of Homs In Large-hollow-core Pbgfsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that this resonant coupling can also effectively suppress higher-order modes of the large mode area hollow-core photonic bandgap fibers [24]. Note that unwanted central core modes can be removed when the effective indices are matched with those of outer core modes.…”
Section: Design Of Spsm-pcfmentioning
confidence: 97%